KAWASAN PRODUKSI SENI PAHAT BATU SEBAGAI DAERAH TUJUAN WISATA DI KABUPATEN MAGELANG - Yuliana Pinaringsih Kristiutami (LPPM Universitas Bina Sarana Informatika, 2014)
Abstract - Development of tourism in Indonesia is currently more important, not only in order to increase the revenue of the country, is expected also to expanding business opportunities, while providing new job opportunities as well as to reduce unemployment. Potential Village Tamanagung as industrial areas and areas of stone carving art craft. Production area of stone carving art has the potential and attraction of attraction so that built and developed as a worthy tourist destination. In the development of tourism in the area of production of stone sculpture studio and the government in cooperation with surrounding communities. The existence of cooperation between organizations institutions with studio owner. Human Resources Training and empowerment of the overall performance of the Department of Tourism. Involving the private sector role in tourism development and promotion is encouraged with the development of technology and information. Designing a stone sculpture gallery as container sales, promotion, recreation and exhibition of handicrafts is a strategy in the development of stone sculpture production region as one tourism destination. Keywords: Development, Stone Sculpture Area, Potential, Attractions, Tourist Destination Abstrak - Pengembangan kepariwisataan di Indonesia saat ini semakin penting, tidak saja dalam rangka meningkatkan penerimaan devisa negara, diharapkan juga dapat memperluas kesempatan berusaha, disamping memberikan lapangan pekerjaan baru juga untuk mengurangi pengangguran. Potensi Desa Tamanagung sebagai daerah industri dan kawasan kerajinan seni pahat batu. Kawasan produksi seni pahat batu mempunyai potensi dan daya tarik wisata berupa atraksi sehingga layak dibangun dan dikembangkan sebagai daerah tujuan wisata. Dalam pengembangan pariwisata di kawasan produksi seni pahat batu pemerintah bekerjasama dengan sanggar dan masyarakat sekitar. Adanya kerjasama antara organisasi lembaga dengan pemilik sanggar. Pelatihan Sumber Daya Manusia, serta pemberdayaan kinerja Dinas Pariwisata secara menyeluruh. Melibatkan peran swasta dalam dalam pengembangan pariwisata serta promosi digalakkan dengan adanya perkembangan teknologi dan informasi. Merancang galeri seni pahat batu sebagai wadah penjualan, promosi, rekreasi dan pameran hasil kerajinan merupakan strategi dalam pengembangan kawasan produksi seni pahat batu sebagai salah satu daerah tujuan wisata. Kata Kunci: Pengembangan, Kawasan seni pahat batu, Potensi, Atraksi, Daerah tujuan wisata